The logistics processes optimization at the warehouse of the enterprise - Shyshkin, Viktor; Nikolov, Mykola (Management and Entrepreneurship: Trends of Development, 2017)
Recently the special attention is drawn to the optimization of the enterprises’ activity in the context of the up-to-date market situation. It is worth to note that the creation of a certain quantity of the material resources stocks is the main condition of the guaranteeing of the manufacturing process continuity. That’s why the logistics processes optimization at the warehouse is becoming increasingly important. There are a lot of the problematic areas in the warehouse logistics. The most important problems, that require optimization, are the unsatisfactory level of the accounting system and information support of the warehouses, the lack of the opportunities for the rapid exchange of the information between all participants of the process, the insufficient level of the resources flow control, the low level of the warehouse operations automation, the lack of the statistics and analysis, which makes it impossible to predict the main indicators, etc. Purpose. The subject of the study is the economic relations developed in the process of the warehouse management at the enterprise. The purpose of the paper is to determine the scientific-grounded proposals for the organization and optimization of the logistics processes at the warehouse. Design/methodology/approach. The basic principles of this research are the causality and objectivity principles, systematic and comparative methods, institutional and structural-functional approach. Findings. In this article the use of the foreign experts’ recommendations, the generalized scheme of the logistics processes at the warehouse optimization and the variants of the methods, which can be used in the practical activity of the enterprises, are suggested. Today the main recommendations for the warehouse operations optimization are: Minimize the number of manual operations. Use the electronic information systems for the warehouse management. Use the logical regulation principle for the material resources at the warehouse. Gather the operational information about the warehouse processes in the real-time operation mode. Implement the innovations gradually. Coordinate the logistics processes at the warehouse with other processes at the enterprise. Set the key performance indicators. Research limitations/implications. The scientific significance of the article consists in the research of the possible ways of the warehouse management system development at the domestic enterprises. Originality/value. The suggested in this article measures will further the increase of the Ukrainian enterprises’ competitiveness and will multiply their financial results. The implementation of the suggested principles and methods of the optimization of the logistics processes at the warehouse will secure the uninterrupted, mutually agreed and effective activity of the enterprises